Variation in ecophysiological traits of dominant species in open and closed stands of a semiarid sandy grassland - Veres, Szilvia (Acta Biologica Szegediensis, 2005)
Under the continental climate of the Carpathian Basin, semiarid grasslands represent one of the widespread vegetation types. Due to overgrazing and other disturbances, most of the semiarid grasslands in Hungary are the mosaics of more or less degraded patches. Our work has focused on the variations in the ecophysiological traits of the common dominant species in a moderately degraded (vegetation cover 70%) and a strongly degraded stand (vegetation cover 27%) of Potentillo-Festucetum pseudovinae community. As a result of low soil moisture content, species experienced significantly higher leaf water saturation deficit in the open stand. Carotenoid pool was larger for all the species in the strongly degraded stand. The protective xanthophyll cycle pool was also higher in the strongly degraded stand, and reached 30–33% of the total carotenoid content. The potential photochemical efficiency (Fv/Fm) was lower for monocot species. There was a decrease in the Fv/Fm values at noon, which was larger in the strongly degraded stand.